Long-term renal function and hypertension in adult survivors of childhood sarcoma: Single center experience. (20th November 2018) - Schiavetti, Amalia; Pedetti, Valeria; Varrasso, Giulia; Marrucci, Oriana; Celani, Camilla; Andreoli, Gianmarco; Bonci, Enea
Abstract: Aim : Little data is available on long-term renal impairment in survivors from childhood sarcoma. We investigated the prevalence of renal impairment and hypertension after very long-term follow-up in survivors who reached adulthood after treatment for childhood sarcoma.Methods: A cross-sectional single center study was performed. Outcomes included estimating glomerular filtration rate (eGFR), albuminuria, glycosuria, serum phosphate and magnesium, tubular reabsorption phosphate (TRP), chronic kidney disease (CKD) according to the "Kidney Disease: Improving Global Outcomes" (KDIGO) guidelines and blood pressure (BP).Results: Out of 87 > 5-year sarcoma survivors, 30 adults (10F/20M, median age at diagnosis 9 years, median age at investigation 26 years, median follow-up 16 years, mean 19 years) were identified. Renal impairment was detected in four cases (13.3%); three of these fulfilled the criteria for CKD. Among the adult survivors, a subgroup of 15 cases (50%) had received ifosfamide without confounding factors such as a diagnosis of genito-urinary rhabdomyosarcoma or administration of other potentially nephrotoxic chemotherapy (platinum-based drugs or methotrexate); no renal dysfunction was detected in this subgroup. In the whole cohort of sarcoma survivors, hypertension was diagnosed in four cases (13.3%); BP was significantly correlated with body mass index [ p .014].Conclusion : In our series of adult survivors treated for a diagnosis of sarcoma in their childhood, the prevalence of CKD was 10%. We found survivors treated with ifosfamide as the only nephrotoxic agent did not present glomerular or tubular toxicity at long term follow-up, but further studies including a larger number of cases are required to confirm it.